An observational study on the association of anti-thyroid autoantibodies with clinical, EEG, MRI, FDG-PET, cerebrospinal fluid and anti-neuronal antibody findings in 530 patients with schizophreniform and affective disorders. (September 2021) - Endres, Dominique; Runge, Kimon; Meixensberger, Sophie; Feige, Bernd; Denzel, Dominik; Pankratz, Benjamin; Maier, Simon; Nickel, Kathrin; Michel, Maike; Venhoff, Nils; Schiele, Miriam A.; Domschke, Katharina; et al.
Abstract: Introduction: Although the link between autoimmune thyroiditis and mental illnesses is well established, the precise underlying pathophysiology and the influence of anti-thyroid antibodies on diagnostic findings require further research. Patients and Methods: A total of 530 patients with schizophreniform and affective syndromes were screened for anti-thyroid antibodies against thyroid peroxidase (TPO), thyroglobulin (TG), and thyroid-stimulating hormone receptor (TSH-R). The patient group analyzed here is a patient subgroup of a previously published cohort (Endres et al., 2020, Translational Psychiatry). The anti-thyroid antibody positive (N = 91) and negative (N = 439) patients were compared in terms of various clinical parameters, routine cerebrospinal fluid (CSF) findings, and the number of positive anti-neuronal antibodies in serum and/or CSF, as well as electroencephalography (EEG), magnetic resonance imaging (MRI), and [18 F] fluorodeoxyglucose positron emission tomography (FDG-PET) findings. Results: Anti-TPO antibodies were increased in 17%, anti-TG antibodies in 15%, and anti-TSH-R antibodies in 2% of all patients. In CSF, higher protein concentrations ( p = 0.018) and albumin quotients ( p = 0.008) were found in the anti-thyroid antibody positive patient group. Also, there were more patients with elevated age-corrected albumin quotients in this group ( p = 0.031). FDG-PET hypometabolism was significantly more frequent and the number of positive anti-neuronal intracellular antibodies was significantly higher in patients with anti-thyroid antibodies ( p = 0.048, N = 29 and p = 0.032, N = 497 respectively). In addition, there was a trend for higher white blood cell (WBC) counts in all patients with anti-thyroid antibodies ( p = 0.090). In the patient subgroup with anti-TPO antibodies this difference was statistically significant ( p = 0.027). No relevant differences were found in the other CSF routine parameters, the number of anti-neuronal antibodies against cell surface antigens in serum and/or CSF, EEG and MRI findings. Discussion: The present study provides evidence of impaired blood CSF barrier (BCSFB) function in patients with anti-TPO and anti-TG antibodies. An influence of anti-TG antibodies on BCSFB structures has been shown in previous laboratory studies, which reported that the antibodies bind to vascular smooth muscle cells. Due to BCSFB breakdown anti-thyroid antibodies might lead to increased autoimmune susceptibility. The alterations in the FDG-PET, WBC count, and anti-neuronal antibody findings against intracellular structures indicate that it could be useful to extend diagnostic investigations in patients with anti-thyroid antibodies. Further studies should investigate whether anti-thyroid antibodies can also act as "drivers of disease". Highlights: Patients with schizophreniform and affective syndromes with anti-thyroid antibodies were compared with patients without these antibodies. Higher protein levels and albumin quotients were identified in the cerebrospinal fluid (CSF) of anti-thyroid antibody-positive patients. Anti-thyroid antibodies might lead to increased autoimmune susceptibility mediated by dysfunction of the blood–CSF barrier. FDG–PET hypometabolism and anti-neuronal intracellular antibodies were observed more frequently in patients with anti-thyroid antibodies. It could be useful to extend diagnostic investigations in patients with anti-thyroid antibodies.